Quality of vegetables in Ghanaian urban farms and markets - Amoah, Philip; Lente, I.; Asem-Hiablie, S.; Abaidoo, Robert C. (2014)
This chapter shows results obtained from analyzing samples of vegetables taken at the farm gate and from selling points in Accra, Kumasi and Tamale. Microbiological data are based on a total of about 1,500 vegetable samples taken from different sampling points along the vegetable distribution chain – farm gates – and from different categories of sellers in Accra, Tamale and Kumasi. Fecal coliforms and helminth eggs were mainly used as the fecal contamination indicator organisms. For chemical contaminants, heavy metals and pesticides in irrigation water and vegetables were analyzed, while estrogens were used as an example for emerging contaminants.